Pengetahuan Ibu Hamil tentang Senam Hamil di Puskesmas Medono Kota Pekalongan - Ni'matul Ulya; Miftachul Jannah (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2023)
Pregnancy is a special condition for a woman as a prospective mother, because during pregnancy there will be physical changes that affect her life. Physical changes that occur sometimes even cause discomfort for the mother, one of which is lower back pain. The results of the study on pregnant women in various parts of Indonesia reached 60-80% of pregnant women experiencing back pain. One way to reduce lower back pain during pregnancy is by doing pregnancy exercises. This study aims to describe the knowledge of pregnant women about pregnancy exercise at the Medono Health Center. This research is quantitative descriptive. Knowledge of pregnant women about the meaning of pregnancy exercise in the sufficient category, as many as 19 respondents (63.2%), about the purpose of pregnancy exercise in the sufficient category as many as 18 respondents (60%), the benefits of pregnancy exercise in the less category as many as 11 respondents (36.6% ), contraindications for pregnancy exercise in the sufficient category were 17 respondents (56.7%), the time for carrying out pregnancy exercise was in the sufficient category as many as 16 respondents (53.2%) and pregnancy exercise movements in the sufficient category as many as 15 respondents (50%). With this research, it is hoped that pregnant women will explore more information related to pregnancy exercise so that the knowledge of pregnant women increases and midwives as health workers can always socialize about pregnancy exercise so that pregnant women know clearly what pregnancy exercise is and its overall benefits.